2018
DOI: 10.1371/journal.pone.0190404
|View full text |Cite
|
Sign up to set email alerts
|

Towards a more practical attention bias test to assess affective state in sheep

Abstract: Tests for attention bias potentially offer more rapid assessment of affective state in animals than existing cognitive methods. An attention bias test has previously been developed for sheep and validated as a measure of anxious states. The 3 minute test assessed behavioural responses of sheep in an enclosed arena after brief exposure to the threat of a dog. Experiment 1 of the current study aimed to refine the previously developed method, removing the need for a habituation period and shortening the test dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(111 citation statements)
references
References 32 publications
6
99
4
Order By: Relevance
“…All latency data were analyzed with Cox's proportional hazards model using survival analysis (Therneau & Grambsch, 2000;Therneau, 2015), as described by Monk et al (2018b). These data included latencies to sniff the photo, sniff the environment and become non-vigilant.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All latency data were analyzed with Cox's proportional hazards model using survival analysis (Therneau & Grambsch, 2000;Therneau, 2015), as described by Monk et al (2018b). These data included latencies to sniff the photo, sniff the environment and become non-vigilant.…”
Section: Methodsmentioning
confidence: 99%
“…Tamir & Robinson, 2007;Grafton, Ang & MacLeod, 2012;Sanchez & Vazquez, 2014;Caudek, Ceccarini & Sica, 2017), although these results have not been consistent in all tested populations (Isaacowitz et al, 2008). In sheep, Lee et al (2016) and Monk et al (2018b) demonstrated that the anxiolytic drug diazepam induced an attention bias away from a threatening stimulus and towards a food reward compared to saline treated control animals. This suggests that the attention bias test may be used to assess positive, or at least less negative, affective states in sheep.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations